Job satisfaction as the mediator between a learning organization and organizational commitment among lecturers - Wang, Gui-Xia; Mat Rashid, Abdullah (RU Publications, 2022)
The higher educational institution needs a group of dedicated and committed lecturers to endure the institution during these turbulent times. As the organizational commitment reflects the self-identification of an employee with the organization, it has far-reaching implications on multifarious aspects in the organization. This present study investigated whether job satisfaction could mediate the relationship between learning organization and organizational commitment. A total of 452 lecturers from Heilongjiang province in China participated in this study. Structural equation modelling showed that job satisfaction significantly mediated the relationship between the dimensions of learning organization and organization, specifically on the effect of continuous learning, connection, and strategic leadership. Job satisfaction is also found to be a stronger predictor of organizational commitment than learning organization. These findings are discussed thoroughly and recommended a holistic plan to be devised that could strengthen learning organization and job satisfaction of lecturers in various aspects of the organization.